The Effect of Digital Health Literacy on HIV/Aids Prevention Behavior Among High School Adolescents in Pamona Puselemba - Sipra Asprilla Sidabutar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to identify the level of digital health literacy, analyze the effect of digital health literacy on HIV/AIDS prevention behavior, and examine measures that can be taken to improve digital health literacy in the prevention of HIV/AIDS among high school adolescents in Pamona Puselemba. The research design used was a One Group Pretest design, with a total sample of 20 respondents. The results show that the level of digital health literacy among students of GKST Senior High School Pamona Puselemba before and after the digital health literacy intervention differed very significantly. There is a significant influence of digital health literacy on HIV/AIDS prevention behavior among high school adolescents in Pamona Puselemba in shaping preventive behaviors against HIV/AIDS. Measures that can be taken to improve digital health literacy in HIV/AIDS prevention among high school adolescents in Pamona Puselemba include integrated education and socialization, digital literacy training, utilization of safe and educational digital platforms, strengthening the role of teachers and parents, student-led digital campaigns, collaboration with medical personnel and positive influencers, and regular evaluation and monitoring.